The evolutionary fate of heterogeneous gene duplications: A precarious overdominant equilibrium between environment, sublethality and complementation. Issue 2 (29th December 2017) - Milesi, Pascal; Assogba, Benoît S.; Atyame, Célestine M.; Pocquet, Nicolas; Berthomieu, Arnaud; Unal, Sandra; Makoundou, Patrick; Weill, Mylène; Labbé, Pierrick
Abstract: Gene duplications occur at a high rate. Although most appear detrimental, some homogeneous duplications (identical gene copies) can be selected for beneficial increase in produced proteins. Heterogeneous duplications, which combine divergent alleles of a single locus, are seldom studied due to the paucity of empirical data. We investigated their role in an ongoing adaptive process at the ace‐1 locus in Culex pipiens mosquitoes. We assessed the worldwide diversity of the ace‐1 alleles (single‐copy, susceptible S and insecticide‐resistant R, and duplicated D that pair one S and one R copy), analysed their phylogeography and measured their fitness to understand their early dynamics using population genetics models. It provides a coherent and comprehensive evolutionary scenario. We show that D alleles are present in most resistant populations and display a higher diversity than R alleles (27 vs. 4). Most appear to result from independent unequal crossing‐overs between local single‐copy alleles, suggesting a recurrent process. Most duplicated alleles have a limited geographic distribution, probably resulting from their homozygous sublethality (HS phenotype). In addition, heterozygotes carrying different HS D alleles showed complementation, indicating different recessive lethal mutations. Due to mosaic insecticide control practices, balancing selection (overdominance) plays a key role in the early dynamics of heterogeneous duplicated alleles; it also favours a high local polymorphism of HS D alleles in natural populations (overdominance reinforced by complementation). Overall, our study shows that the evolutionary fate of heterogeneous duplications (and their long‐term role) depends on finely balanced selective pressures due to the environment and to their genomic structure.